Konsep Talak Perspektif Wahbah Az-Zuhaili, Muhammad Jawad Mughniyah, dan Kompilasi Hukum Islam - Arista Yuniarti; Saifullah Saifullah (Journal of Economics, Law, and Humanities, 2023)
Jurisprudence prioritizes the right of divorce to be held by the husband. The purpose of this qualitative research with a literature study approach is to describe and analyze: 1) the concept of divorce, which can cause the breakup of marriage relations according to Wahbah Az-Zuhaili, Muhammad Jawad Mughniyah, and the Compilation of Islamic Law, and 2) what is the legal term used by Wahbah Az-Zuhaili, Muhammad Jawad Mughniyah, and the Compilation of Islamic Law (KHI) in determining divorce. The results of this study indicate whether the husband intends to become the legal ruler or not to divorce and prohibit divorce without any cause. The difference lies in the editorial divorce used and the witness in the divorce. As for instituting the law of Wahbah Az-Zuhaili, Muhammad Jawad Mughniyah both used the Al-Qur'an, Sunnah, and ijmak. The difference lies in the way of understanding sunnah and ijmak. Jawad does not use kiyas in determining the law but uses reason so that the relevance of the divorce provisions of the two figures, namely Wahbah Az-Zuhaili, Muhammad Jawad, and KHI, in determining the divorce issue lies in the procedure for its implementation. According to the two figures, divorce does not need to be done in front of the courtroom wherever the divorce is pronounced, so divorce falls at that moment because divorce is the husband's right. However, in Indonesia, divorce must be carried out before a court hearing because the husband cannot guarantee his right to divorce. Also, the wife gets protection and legal certainty.